SHORT-ROOT Deficiency Alleviates the Cell Death Phenotype of the Arabidopsis catalase2 Mutant under Photorespiration-Promoting Conditions. Issue 8 (18th July 2016) - Waszczak, Cezary; Kerchev, Pavel I.; Mühlenbock, Per; Hoeberichts, Frank A.; Van Der Kelen, Katrien; Mhamdi, Amna; Willems, Patrick; Denecker, Jordi; Kumpf, Robert P.; Noctor, Graham; Messens, Joris; Van Breusegem, Frank
Abstract : The photorespiratory phenotype of the CATALASE2-deficient Arabidopsis mutant is alleviated in the absence of the SHORT-ROOT transcription factor. Abstract: Hydrogen peroxide (H2 O2 ) can act as a signaling molecule that influences various aspects of plant growth and development, including stress signaling and cell death. To analyze molecular mechanisms that regulate the response to increased H2 O2 levels in plant cells, we focused on the photorespiration-dependent peroxisomal H2 O2 production in Arabidopsis thaliana mutants lacking CATALASE2 (CAT2) activity ( cat2-2 ). By screening for second-site mutations that attenuate the PSII maximum efficiency (Fv '/Fm ') decrease and lesion formation linked to the cat2-2 phenotype, we discovered that a mutation in SHORT-ROOT (SHR) rescued the cell death phenotype of cat2-2 plants under photorespiration-promoting conditions. SHR deficiency attenuated H2 O2 -dependent gene expression, oxidation of the glutathione pool, and ascorbate depletion in a cat2-2 genetic background upon exposure to photorespiratory stress. Decreased glycolate oxidase and catalase activities together with accumulation of glycolate further implied that SHR deficiency impacts the cellular redox homeostasis by limiting peroxisomal H2 O2 production. The photorespiratory phenotype of cat2-2 mutants did not depend on the SHR functional interactor SCARECROW and the sugar signaling component ABSCISIC ACID INSENSITIVE4, despite the requirement for exogenous sucrose for cell death attenuation in cat2-2 shr-6 double mutants. Our findings reveal a link between SHR and photorespiratory H2 O2 production that has implications for the integration of developmental and stress responses.